2016
DOI: 10.1002/jctb.4893
|View full text |Cite
|
Sign up to set email alerts
|

High production yield and specific productivity of succinate from cassava starch by metabolically-engineeredEscherichia coliKJ122

Abstract: BACKGROUND Succinate has been widely used in chemical industries and its microbial production is a desirable option. The feasibility of bio‐based succinate production on an industrial scale strongly depends on the utilization of cheaper renewable resources. The use of cassava starch may make the fermentation process of succinate more economically competitive. RESULTS Simultaneous saccharification and fermentation (SSF) of succinate production was performed in minimal salt medium containing a cheap cassava star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…For example, succinic acid and 1,4‐BDO, both of which are used for the synthesis of PBS as monomers, have successfully been produced by employing metabolically engineered microorganisms in significant yields suitable for commercial production (Table 1 and Figure 2). [ 57–74 ] In particular, the production of succinic acid is currently being replaced by biological production and several companies already produce bio‐succinic acid in an industrial scale. [ 94,100 ] Similar to PBS, all monomers of PBAT, such as 1,4‐BDO, adipic acid, and even TPA, can also be produced by engineered microbial strains (Table 1 and Figure 2).…”
Section: Biodegradable Biopolymersmentioning
confidence: 99%
“…For example, succinic acid and 1,4‐BDO, both of which are used for the synthesis of PBS as monomers, have successfully been produced by employing metabolically engineered microorganisms in significant yields suitable for commercial production (Table 1 and Figure 2). [ 57–74 ] In particular, the production of succinic acid is currently being replaced by biological production and several companies already produce bio‐succinic acid in an industrial scale. [ 94,100 ] Similar to PBS, all monomers of PBAT, such as 1,4‐BDO, adipic acid, and even TPA, can also be produced by engineered microbial strains (Table 1 and Figure 2).…”
Section: Biodegradable Biopolymersmentioning
confidence: 99%
“…The enzymatic hydrolysis condition was investigated to ensure complete hydrolysis of the cassava starch to fermentable sugars. From previous works, the steps of gelatinization and hydrolysis using α‐amylase were performed at the same time 29,30 . Therefore, the experiment was first conducted by the addition of α‐amylase enzyme before gelatinization.…”
Section: Resultsmentioning
confidence: 99%
“…In general, a conventional biochemical production process from starch requires gelatinization and liquefaction followed by the saccharification step with high amounts of α‐amylase and glucoamylase to completely hydrolyze starch to glucose prior to fermentation. In the conventional process, Khor et al 30 . revealed that the liquefaction step was usually initiated by adding an α‐amylase enzyme to the cassava starch slurry before autoclaving.…”
Section: Discussionmentioning
confidence: 99%
“…Bio-based succinate is mostly produced in a monosaccharide-based biorefinery platform, using microorganisms such as Actinobacillus succinogenes, Anaerobiospirillum succiniciproducens, Mannheimia succiniciproducens, and a recombinant Escherichia coli strain (Bozell and Petersen, 2010;Rakshit, 2004). Succinate production from cassava starch has been tested using metabolically-engineered Escherichia coli KJ122, but a biological pretreatment by adding hydrolytic enzyme was required (Khor et al, 2016). So far, succinate production from biomass-derived hydrolysates has not been established (Salvachúa et al, 2016).…”
Section: Characteristic / Strainmentioning
confidence: 99%